Experimenting with the transition rule in dynamic games - Emanuel Vespa; Alistair J. Wilson (Quantitative Economics, 2019)
In dynamic environments where the strategic setting evolves across time, the specific rule governing the transitions can substantially alter the incentives agents face. This is particularly true when history-dependent strategies are used. In a laboratory study, we examine whether subjects respond to the transition rule and internalize its effects on continuation values. Our main comparison is between an endogenous transition where future states directly depend on current choices, and exogenous transitions where the future environment is random and independent of actions. Our evidence shows that subjects readily internalize the effect of the dynamic game transition rule on their incentives, in line with history-dependent theoretical predictions.
Keywords: C73; C92; D90; 330; Dynamic games; state transition rule; history dependent play